Determination of the N-terminal amino acid sequence of the purified prothrombin from a patient with liver cirrhosis - (:unkn) unknown (PERGAMON-ELSEVIER SCIENCE LTD, 2000)
The reasons for the decreased functional activity of prothrombin in liver diseases are still speculative. When a highly purified preparation of prothrombin from a patient with liver cirrhosis is available, the cause of prothrombin abnormalities may be researched on, a molecular basis. In this study, prothrombin (6.7 mg) was purified from the ascites fluid (1130 mL) of a patient with liver cirrhosis by barium citrate adsorption, ammonium sulfate elution, DEAE Sephacel and Heparin Sepharose CL-6B column chromatography steps. The molecular weight of this prothrombin was the same as that of normal prothrombin purified from a normal plasma pool. The specific activities were found to be 3.36 U/mg in the one stage clotting assay and 28.9 U/mg in the staphylocoagulase/chromogenic substrate assay, while the normal prothrombin specific activities were 3.92 U/mg and 30.1 U/mg respectively. When N-terminal amino acid sequence analysis was carried out, it was seen that the first 20 residues were identical to the normal human prothrombin excepting the Gla at position #14. (C) 2000 Elsevier Science Ltd. All rights reserved.
Keywords: prothrombin purification; amino acid sequence; ascites fluid; cirrhosis; DES-GAMMA-CARBOXYPROTHROMBIN; BLOOD-COAGULATION PROTEINS; HEPATOCELLULAR-CARCINOMA; VITAMIN-K; CARBOXY PROTHROMBIN; CARBOXYGLUTAMIC ACID; SERUM; BINDING; IMMUNOASSAYS; DIAGNOSIS